A Catalog of Diffuse Interstellar Bands in Fullerene-Containing Planetary Nebulae. Issue Volume 9:Issue S297(2013) (21st February 2014) - Manchado, A.; Díaz-Luis, J. J.; García-Hernández, D. A.; Cataldo, F.
Abstract: Large fullerenes and fullerene-based molecules have been proposed as carriers of diffuse interstellar bands (DIBs). The recent detection of the most common fullerenes (C60 and C70 ) around some Planetary Nebulae (PNe) now enable us to study the DIBs in fullerene-rich space environments. We have studied the presence of DIBs in the optical spectra ( 3300-9400 Å) of two fullerene-containing PNe (Tc 1 and M 1-20). Special attention is given to DIBs which are found to be unusually intense in fullerene-containing PNe; several of these DIBS have not previously been reported. Fullerenes larger than C60 (and C70 ) and multishell fullerenes may be possible candidate carriers for the unusual DIBs seen in fullerene-rich environments.